Mrs. Darcy and the blue-eyed stranger : new and selected stories - Smith, Lee, 1944- (Algonquin Books of Chapel Hill, 2010)
Collects fourteen stories--seven brand-new ones along with seven favorites from Smith's three earlier collections--about characters such as an eight-year-old boy obsessed with vocabulary words, a young bride who has married "way up," and Mrs. Darcy herself, an older woman making it through widowhood her own way.